PERSEPSI NASABAH TERHADAP SISTEM PEMBIAYAAN BAGI HASIL DI BANK JABAR SYARIAH KOTA CIREBON - Zuardi, Muhammad Hanafi (P3M STAIN Jurai Siwo Metro, 2013)
Financing for the results that are usually applied in the Islamic banking business is divided into two groups: mudharaba and musharaka. How does a bank present for the result of financing product? It must be based on the basic Islamic rules and regulations. For a customer can also conduct it wisely in every transaction which is still and has been done. By knowing the background of different individuals, it will produce a different perception. The study of perception in financing for the result is preferred. This is because in order to know how the relationship a customers to finance for the result that has been and are being done. Beside knowing how the relationship a costumer to finance for the result, it will also discuss what the factors that influence the customer perception to finance for the results, which is in this case we restrict to six factors: age, gender, educational level, occupation, income level, and a persons level of religiosity. The method used in this study is a descriptive analysis (mean and standard deviation calculation). As well as multiple regression analysis. Prior to the analysis, all the data that has been collected respondents had conducted a test of the validity and reliability testing as a sign of whether the data obtained from respondents are valid and can be done in the next stage of analysis. The total of all respondent samples in this study were 316 clients, 305 people are Musharaka and 11 people are Mudaraba. From the analysis conducted, the perception of consumers have an excellent relationship to finance for the results at Bank Syariah Cirebon West Java. As some of the factors that have been identified earlier, where the measurement of perception assessed by three (3) indicators: cognitive, affective, and psychomotor, it turns out the six factors are: age, sex, education, occupation, income level and religiosity very affect the formation of customer perception of 69.7%. And of the six factors, only the factor that religiosity is acceptable because it has a good level of significance, that is 0.0001 Keywords: Finance, Islamic banking, profit and los-sharing, religiosity